Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

If f(x) = 2x + 10, then f^-1(x) =


Sagot :

If [tex]f^{-1}(x)[/tex] is the inverse of [tex]f(x)[/tex], then

[tex]f\left(f^{-1}(x)\right) = x[/tex]

by definition of inverse function. We have

[tex]f\left(f^{-1}(x)\right) = 2f^{-1}(x) + 10 = x[/tex]

Solve for the inverse :

[tex]2f^{-1}(x) + 10 = x \\\\ 2f^{-1}(x) = x-10 \\\\ \boxed{f^{-1}(x) = \dfrac{x-10}2}[/tex]